Art Gallery Education in New Zealand during COVID-19: The Emergence of a Community of Practice. Issue 1 (1st July 2020) - McNaughton, Esther Helen
Abstract: This article describes the unprecedented coming together of New Zealand art gallery educators to respond to the challenges of the 2020 COVID-19 pandemic. This newly formed community of practice met virtually three times at critical points. At each stage, new concerns were discussed and understandings evolved. The gallery educators were able to approach shared issues cooperatively, enabling mutual support to a degree that had hitherto not been possible. By the end of these meetings, gallery educators were reestablishing their regular teaching practice with the integration of many of the innovations of the period. Additionally, the meetings fulfilled a preexisting desire for closer contact and professional support, and thus proved to be the foundation of an ongoing national professional group for New Zealand art gallery educators.